Knowledge Attitude and Practices towards prevention of Diabetes Mellitus among Patients aged 25-70 years in Wakiso Health Centre IV, Wakiso District. A Cross-sectional Study. - Malunga , Bridget Charity (Student’s Journal of Health Research Africa, 2022)
Background: Africa is estimated to have 15.9 million adults living with DM which is a regional prevalence of 3.1%. The purpose of the study was to determine the knowledge, attitudes, and practices toward the prevention of diabetes mellitus among patients aged 25-70 years in Wakiso health center IV Wakiso district. Methodology: The study employed a descriptive cross-sectional design; a simple random sampling technique was used. Data were analyzed manually by use of tally sheets and were entered in the excel computer program to generate tables, graphs, and pie charts. Results: The study findings on knowledge towards prevention of DM showed that (88%) of the respondents had never heard about diabetes, (62%) did not know the different types of diabetes, (and 56%) knew that eating too many sugary things causes diabetes, (50%) knew diabetic food as one of the complications of DM, (44%) knew over urinating as a symptom and a sign of diabetes and (50%) agreed that dietary modification is a preventive measure for DM. (60%) agreed that blood sugar can be controlled by having the right diet, (56%) agreed that they needed to check their blood sugar regularly, (and 48%) thought they should be checked for diabetes, (80%) wished to follow advice on preventions of DM and (56%) agreed that DM complications can be prevented. Conclusion: Participants had fair knowledge, and with favorable attitude towards the prevention of diabetes mellitus but poor practices were noticed since most patients had never screened for DM, and performed physical excises occasionally. Recommendation: The researcher recommended that; health workers at Wakiso health center IV should continue to educate patients on the benefits of regular exercise, the right diet, and screening to implement better behavior of change and this will reduce DM cases at the facility.